(5v+6)(4-v)=0

Simple and best practice solution for (5v+6)(4-v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5v+6)(4-v)=0 equation:


Simplifying
(5v + 6)(4 + -1v) = 0

Reorder the terms:
(6 + 5v)(4 + -1v) = 0

Multiply (6 + 5v) * (4 + -1v)
(6(4 + -1v) + 5v * (4 + -1v)) = 0
((4 * 6 + -1v * 6) + 5v * (4 + -1v)) = 0
((24 + -6v) + 5v * (4 + -1v)) = 0
(24 + -6v + (4 * 5v + -1v * 5v)) = 0
(24 + -6v + (20v + -5v2)) = 0

Combine like terms: -6v + 20v = 14v
(24 + 14v + -5v2) = 0

Solving
24 + 14v + -5v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(4 + -1v)(6 + 5v) = 0

Subproblem 1

Set the factor '(4 + -1v)' equal to zero and attempt to solve: Simplifying 4 + -1v = 0 Solving 4 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1v = 0 + -4 -1v = 0 + -4 Combine like terms: 0 + -4 = -4 -1v = -4 Divide each side by '-1'. v = 4 Simplifying v = 4

Subproblem 2

Set the factor '(6 + 5v)' equal to zero and attempt to solve: Simplifying 6 + 5v = 0 Solving 6 + 5v = 0 Move all terms containing v to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5v = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5v = 0 + -6 5v = 0 + -6 Combine like terms: 0 + -6 = -6 5v = -6 Divide each side by '5'. v = -1.2 Simplifying v = -1.2

Solution

v = {4, -1.2}

See similar equations:

| .25x+.1x=9.8 | | 3[(1)]=x | | 2p+22p^2-p= | | 3[(1)]= | | x^2+31x+5=0 | | Y=-5x+18 | | 24p-28q= | | .25y-10=.1y | | 17+5/15=-4 | | .4x-4=2.8+.2x | | (s/3)+11=16 | | 7+9+x=40 | | 1.12+1.15x=8.62 | | -4t^2+30t-12=0 | | 6-7m-20m^2=0 | | -16+51=-5(x+5) | | 1.12+1.12x=8.62 | | 5=4x-10 | | 8x^2+kx+k=0 | | (4z+1)(8-z)=0 | | 17x-5=11x-35 | | 22+4b=-2(1-6b) | | -0.7x+9.24=-0.5x+8.24 | | -0.7+9.24=-0.5+8.24 | | 3(2x-4)+5=15 | | 9=x/5-1 | | b-7=-4 | | 68=-16t^2-64t-12 | | r-5=20 | | 0.7x-0.5x-6=-4 | | 45(6x)=303 | | 1/4+4x/5=20 |

Equations solver categories